KEPEMIMPINAN DALAM MENGELOLA PERUBAHAN DAN INOVASI ORGANISASI (KAJIAN LITERATUR) - La Ode Muhammad Ichwan Sjachrawy; Muhammad Masri (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
Change and innovation are strategic needs for organizations in facing the dynamics of globalization, technological developments, and demands for improved performance. This article aims to examine the concept of leadership in managing organizational change and innovation based on Yukl's (2013) perspective in the discussion of Leading Change and Innovation through a literature review approach. The results of the study indicate that leadership plays a central role as an agent of change capable of building a vision, managing resistance, encouraging innovation, and creating an adaptive organizational culture. Innovative, adaptive, collaborative, and digital leadership has been proven to contribute to increased organizational effectiveness, the quality of public services, the success of bureaucratic reform, and sustainable organizational transformation. In addition, human resource development and the utilization of information technology are important supporting factors in creating a resilient, responsive, and competitive organization in a constantly changing environment.